ANALISIS PENGARUH EKUITAS MEREK, PERSAINGAN, KEPERCAYAAN DAN KEMUDAHAN TRANSAKSI TERHADAP MINAT BELI PRODUK THE EXECUTIVE - Sheli Nada Triningsih; Heny kurnianingsih (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
Abstract The purpose of this research is to see the effect of brand equity, competition, trust and ease of transaction on buying interest in The Executive's products. Data was collected through the distribution of online questionnaires to The Executive's customers. Research proves that the element of brand equity has a significant effect on buying interest, while competition, trust, and ease of transaction have no significant effect. Keywords: Brand Equity, Competition, Trust, Ease of Transaction, Buying Interest.